Impact of two physical exercise social programs on seniors fall risk - Alves Camelo, Janaína; Porto Flávia; Assumpção Harris Elizabeth Rose; da Penha Santos, Cintia; Lima da Silva Nádia Souza (Cuerpo, Cultura y Movimiento, 2023)
The aim of this study was to compare the impact of physical exercise on the risk of falls in older adults participating in two social programs. Thirty volunteers participated, divided into two groups: Con Burden (GCC), with 11 women and 4 men (75.4±9.1 years) participating in a university extension project, and Sem Carga (GSC), with 12 women and 3 men (66.9±4.2 years) who exercised at an outdoor gym in the same geographic region. GCCs and GSCs were similar in terms of female predominance, while GCCs are longer-lived (p=0.008). Every participant underwent physical-functional assessment with the Berg Balance Scale. The difference between groups was assessed using the Mann-Whitney test (p ≤ 0.05). Data analysis found no significant difference between the groups regarding the results of the MSA (p=0.2) and both groups had a low risk of falling.